Pemetaan Peran dan Kolaborasi Stakeholder dalam Pengelolaan Ekowisata serta Pengembangan Ekonomi Kreatif Sentra Tapis Lampung di Desa Wisata Lugusari, Provinsi Lampung - Cahyo, Enggar Dwi; Astriyantika, Meyliana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
The latest tourism development is focused on the attraction of living activities and rural resources by highlighting various potential regional authenticity. As a derivative of the concept of sustainable tourism development, the development of tourism villages directly contributes to the preservation and introduction of local culture, superior agricultural and plantation activities, as well as triggering the creation of various creative ideas to support the local economy. The selection of this research location was based on research that the Governor of Lampung Province had issued a 2022 decree determining 3 tourism villages focused on developing Lampung Tapis centers, one of which was Lugusari Tourism village, Pagelaran District, Pringsewu Regency. This was welcomed very positively by various welcome who involved themselves directly in developing and promoting various potentials and attractions in the Lugusari Tourism village. Seeing the large number of contributes entering, it is important to identify each stakeholder and carry out role mapping so that the direction of effective and optimal collaboration can be seen. Data were collected by observation, interviews, and literature studies, then analyzed descriptively qualitatively. Based on the research results, it was identified that the tourism pentahelix plays an active role in the management of the Lugusari Tourism village which includes government, private, academic, media, and especially the community stakeholders. The flow of stakeholder coordination in the Lugusari Tourism village is centered on the village government which is at the lead of control regarding regulatory direction, ideas, concepts and program implementation as well as controlling the management conditions of the Lugusari Tourism village. Furthermore, the role of stakeholders in Lugusari Tourism village is divided into 5, namely policy creator (government), Regulator (government), Facilitator (government, academics, business and media), Accelerator (Business and Media), and Implementer (Community).